Empirical antibiotic therapy for pneumonia in intensive care units: a multicentre, retrospective analysis of potentially pathogenic microorganisms identified by endotracheal aspirates cultures - Scholte, J. B. J. (Eur J Clin Microbiol Infect Dis, 2015)
The purpose of this investigation was to explore the presumed relationship between the days of hospitalisation and microorganisms identified by endotracheal aspirate cultures in relation to adequate empirical treatment strategies of pneumonia in the intensive care unit (ICU). All potentially pathogenic microorganisms identified by (surveillance) cultures of endotracheal aspirates obtained in the ICUs of two Dutch teaching hospitals in 2007 and 2012 were retrospectively collected and analysed. Antibiotic susceptibilities to 11 antibiotics were calculated for several time points (days or weeks) after hospital admission and expressed per patient-day. In total, 4184 potentially pathogenic microorganisms identified in 782 patients were analysed. Prevalence of the classic early-onset pneumonia-causing microorganisms decreased from 55 % on the first four days to 34 % on days 4–6 after hospital admission (p < 0.0001). Susceptibility to amoxicillin/clavulanic acid was below 70 % on all days. Except for days 0 and 12, susceptibility to ceftriaxone was below 80 %. The overall susceptibility to piperacillin/tazobactam was 1518/1973 (77 %) in 2007 vs. 727/1008 (67 %) in 2012 (p < 0.0001). After day 8 of hospital admission, susceptibility to piperacillin/tazobactam therapy was below 80 % in 2012. After one week of hospital admission, susceptibilities to antibiotics were lower in the hospital that included that antibiotic in the local empirical treatment protocols as compared to the hospitals in which that antibiotic was not or infrequently included: 90/434 (21 %) vs. 117/398 (29 %); p = 0.004 for amoxicillin/clavulanic acid and 203/433 (47 %) vs. 253/398 (64 %); p < 0.001 for ceftriaxone. No cut-off in the number of days after hospital admission could be identified to distinguish early-onset from late-onset pneumonia. Consequently, the choice of empirical antibiotics should probably not be based on the time of onset. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10096-015-2482-y) contains supplementary material, which is available to authorized users.